The Analysis Of Factors Influencing Management of Medical Solid Waste of Hazardous and Toxic Materials (B3) at RSUD. Dr. H. Kumpulan Pane, Tebing Tinggi City on 2024 - Pulungan, Desi Erni Dewi; Achmad Rifai; Fadlilah Widyaningsih3 (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Dr. H. Kumpulan Pane Regional Hospital, Tebing Tinggi City has 213 beds with a potential medical waste calculation of around 682 kg per day, but data from the last 3 months shows that B3 waste at Dr. H. Kumpulan Pane Regional Hospital is 79,142/kg/month or approximately 2,638 kg/day. Objectives: to analyze the factors that influence the management of solid media waste of hazardous and toxic materials at RSUD.Kumpulan Pane, Tebing Tinggi City. Research method: This research is a quantitative descriptive research with a cross sectional design. Results: In this study, momentary measurements were carried out on independent variables and concurrent variables (Point time approach), with the T test and F test, the results obtained were that the knowledge factor of sanitation officers did not affect the management of B3 medical solid waste, the infrastructure factor did not affect the management of B3 medical solid waste, the technical guideline factor did not affect the management of B3 medical solid waste, but the funding factor affected the management of B3 medical solid waste at the Hospital. Conclusion: The most influential factor among the four variables is the funding factor variable with a Beta value of 0.96.